Adaptability of Kemenyan Toba (Styrax sumatrana) and Suren (Toona sureni) On Gold Mining Tailing - Susilowati, Arida; Ahmad, Alfan Gunawan; Sirait, David Raymod (Talenta Publisher, 2019)
Tailing was residue of gold mining process which lead to some environment problem. Beside containing heavy metal, tailing have lower soil fertility, physical, chemical and biological characteristics. To overcome this problem, revegetation activities was needed. The succesfulness of revegetation activities determined by adaptive trees selection. Local species was recommended because suitable to local climate and soil conditions, in this study we choosed toba benzoin (Styrax sumatrana) and suren (Toona sureni). The objective of this research was to get information about adaptability of toba benzoin and suren on growth media containing tailings. Research was conducted in green hause Faculty of Agriculture, University of Sumatera Utara. Factorial Randomized Completely Design with two factor were used in this research. The first factor was growing media (Factor A) and the second factor was seedling species (Factor B). The observed parameter were seedling height, seedling diameter, seedling dry weight, primary root lenght, shoot-root ratio and chemical properties of media. The results showed that the species and growing medium significantly affected the height growth of seedlings, seedling diameter, seedling dry weight and length of the primary root. The addition of topsoil and compost able to improve the chemical properties of the tailings are used. Tailings media and compost with composition ratio of 1:1 is recommended for Toba benzoin and Suren. That media provide the most optimal results of Toba benzoin and suren growth.